A retrospective study of thoracic endovascular aortic repair timing in patients with uncomplicated type B dissection who have a smoking history - Gao, Hui-Qiang; Li, Guoqi; Zhang, Hong-Kai; Zhang, Lan-Lin; Xu, Shang-Dong (Frontiers in Cardiovascular Medicine, 2022)
Objective: To determine the optimal timing of thoracic endovascular aortic repair (TEVAR) for patients with uncomplicated type B dissections who have a smoking history. Methods: Data from 308 consecutive patients with uncomplicated type B dissections, who have a smoking history and onset-to-TEVAR time within 90 days, were analyzed. The patients were divided into two groups: acute and subacute phases. Univariate and multivariate regression analyses were performed. Smooth curve fitting and threshold analysis were performed to characterize the relationship between the onset-to-TEVAR time and follow-up deaths. Results: There were no significant differences between the two groups. Smooth curve fitting and threshold effect analysis showed that if early TEVAR was performed within 9.4 days from onset, there was better long-term survival and there was no significant difference after 9.4 days. Conclusion: By studying the relationship between onset-to-TEVAR time and all-cause mortality, we found that early TEVAR may have a lower all-cause mortality rate during follow-up in uncomplicated type B dissection patients who have a smoking history and within 90 days from onset.